Talc powder, agent for improving resin physical properties, and resin composition
Talc powder with specific properties and manufacturing methods improves resin compositions by enhancing dispersibility and physical properties, addressing the limitations of conventional talc powders in thermoplastic resins.
Patent Information
- Application Number
- JP2023115778
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
AI Technical Summary
Existing talc powders do not adequately consider dispersibility and physical property enhancement when added to thermoplastic resins, limiting their effectiveness in achieving high material design properties.
Talc powder with a weight loss rate of 0.180% by mass or less, median diameter of 1 to 10 μm, bulk density of 0.10 to 0.35 g/cm³, and BET specific surface area of 3 to 20 m²/g, manufactured using a steam jet mill to enhance hydrophobicity and bulkiness, is used to improve resin compositions.
The talc powder significantly enhances the physical properties of resin compositions, particularly elastic modulus, when incorporated, surpassing conventional talc powders in resin material improvements.
Smart Images

Figure 2025012720000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a talc powder, a resin property improver, and a resin composition. [Background technology]
[0002] When producing resin molded products, various fillers are mixed with the resin raw materials to improve physical properties such as mechanical strength. One such filler that is widely used is talc. Talc is the softest of all rock-forming minerals, has cleavage properties that make it easy to peel off, has a smooth feel, and is chemically stable, so it is widely used in combination with various raw materials.
[0003] Due to its excellent versatility, talc is used in a wide range of fields, such as plastics (resins), papermaking, cosmetics, medicines, fertilizers, paints, ceramics, etc. For example, resin compositions containing talc are widely used in various fields, such as automobile parts, home appliance parts, and office equipment parts.
[0004] On the other hand, with the advancement of technology in various fields, there is a growing tendency to try to achieve a high level of physical properties at the material design stage. Various improvements have been made to the widely used talc in order to bring out its inherent useful physical properties.
[0005] For example, Patent Document 1 describes a granular talc obtained by degassing and then compressing powdered talc having an average primary particle size of 0.1 to 10 μm without directly compressing it, and the bulk density is 0.6 to 0.94 g / cm. 3 Talc having a destruction rate of 70 to 100% by weight has been proposed. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2005-104794 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, although Patent Document 1 examines whether the dispersibility is excellent when added to a thermoplastic resin and melt-mixed, it does not examine whether the resin properties (e.g., properties such as flexural modulus) can be improved. In other words, it cannot be said that it is an attempt to realize a high level of physical properties at the material design stage.
[0008] In view of the above, an object of the present invention is to provide a talc powder that, when added to a resin composition, can improve the physical properties of the resin as compared to the case where a conventional talc powder is added. [Means for solving the problem]
[0009] As a result of intensive research aimed at solving the above problems, the present inventors have found that the problems can be solved by the present invention described below.
[0010] [1] A talc powder having a weight loss rate of 0.180 mass% or less by thermogravimetric differential thermal analysis at 100 to 450°C and a median diameter (D50) of 1 to 10 μm. [2] BET specific surface area is 3 to 20 m 2 / g of the talc powder according to [1]. [3] Bulk density: 0.10 to 0.35 g / cm 3 The talc powder according to [1] or [2], [4] A resin property improver comprising the talc powder according to any one of [1] to [3]. [5] A resin composition comprising the talc powder according to any one of [1] to [3] and a resin. Effect of the Invention
[0011] According to the present invention, it is possible to provide a talc powder which, when added to a resin composition, can improve the physical properties of the resin as compared to the case where a conventional talc powder is added. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] [Talc powder] The talc powder according to one embodiment of the present invention (present embodiment) has a weight loss rate of 0.180 mass % or less as measured by thermogravimetric differential thermal analysis at 100 to 450°C.
[0013] The weight loss rate of 0.180% by mass or less indicates that the amount of water present on the conventional talc powder is very low. In other words, it can be inferred that the talc powder is in a highly hydrophobic state, which increases its affinity with resin and is believed to improve the physical properties of the resin (especially the elastic modulus). The weight loss rate is preferably 0.1750% by mass or less, more preferably 0.1670% by mass or less, and even more preferably 0.1450% by mass or less.
[0014] The weight loss rate by thermogravimetric differential thermal analysis can be determined, for example, by measuring using a known device according to the following method. A 7 mg sample of talc powder is placed in a differential thermobalance (for example, ThermoPlus2, manufactured by Rigaku Corporation) and heated (from room temperature to 950°C), during which the weight loss rate (mass%) is determined from 100°C to 450°C. The heating rate is 10°C / min. The measurement atmosphere is preferably a nitrogen atmosphere. Here, by setting the temperature to 100 to 450° C., the weight loss rate caused by the hydroxyl groups in the talc powder can be measured with high accuracy.
[0015] In order to make the weight loss rate according to this embodiment 0.180% by mass or less, for example, it is preferable to pulverize the raw material talc under conditions of higher temperature and higher shear force than the pulverization conditions using a normal jet mill. Specifically, it is preferable to prepare the talc by adjusting the temperature, pressure, etc., using a pulverization means that can instantaneously apply high shear force at high temperature using superheated steam (saturated steam and steam obtained by further heating the saturated steam) as fluid energy, such as a steam jet mill described later.
[0016] In this embodiment, the bulk density (solidification) of the talc powder is 0.10 to 0.35 g / cm 3 and preferably 0.12 to 0.30 g / cm 3 More preferably, the density is 0.15 to 0.28 g / cm 3 It is more preferable that the density is 0.10 to 0.35 g / cm. 3 This makes it easier to obtain a higher elastic modulus when mixed with a resin.
[0017] The above-mentioned bulk density indicates that the talc powder of this embodiment is in a very bulky state. Usually, the particle size and aspect ratio of the talc powder are designed to be optimal, assuming that the bulk density is high, taking into consideration handling such as transportation. In contrast, this embodiment focuses on a "low bulk density state (= very bulky state)" that is likely to be excluded from consideration based on technical common sense, and the present invention was arrived at with an idea that is not bound by ordinary technical common sense.
[0018] Here, the bulk density can be determined by the packed bulk density measured using a powder property evaluation device (Powder Tester PT-X manufactured by Hosokawa Micron Corporation). The measurement conditions are as follows: a sample is supplied to a sieve with an opening of 710 μm, and the sample is sieved at 100 cm with an amplitude of 1.5 mm. 3 Add the sample so that the powder surface position of the cap placed on the bulk density measurement cup remains constant, and tap 180 times.
[0019] In order to obtain a high elastic modulus when mixed with a resin, the median diameter (volume basis, D50) of the talc powder according to the present embodiment is 1 to 10 μm, preferably 1.5 to 9.5 μm, and more preferably 1.7 to 8.5 μm. More specifically, D50 is preferably 2.3 to 8 μm, and more preferably 3 to 7 μm.
[0020] Here, the median diameter can be determined as the volume-based median diameter (D50: particle diameter at 50% of the cumulative volume from the small particle side) by measuring the particle size distribution using a laser diffraction particle size distribution analyzer (SALD-200V ER, manufactured by Shimadzu Corporation).
[0021] The specific surface area (BET specific surface area) of the talc powder of this embodiment is 3 to 20 m 2 / g, and preferably 3 to 18m 2 / g, and 6.0 to 16.0 m 2 / g, more preferably 6.5 to 15.0 m 2 More preferably, the range is 6.5 to 14.0 m / g. 2 Even more preferably, it is / g. Specific surface area is 3 to 20 m 2 / g, a high elastic modulus can be obtained when mixed with a resin. Here, the specific surface area can be determined by measuring using a specific surface area / pore distribution measuring device (BELSORP MINIII manufactured by Microtrack-Bell Co., Ltd.). As sample preparation, it is preferable to dry the sample at 100° C. for 90 minutes using a vacuum dryer.
[0022] The talc powder according to the present embodiment is preferably natural talc (non-synthetic talc) rather than synthetic talc. Synthetic talc is talc produced by chemical synthesis, for example, obtained by hydrothermal synthesis in which raw materials containing magnesium and silicon are heated at high temperature under pressure. On the other hand, natural talc is a mineral that occurs naturally. Natural talc may contain calcium carbonate, dolomite, and the like as trace components. Such trace components have the function of improving impact resistance when added to a resin. Therefore, natural talc powder is preferable as the talc powder according to the present embodiment.
[0023] [Talc powder manufacturing method] The method for producing talc powder according to this embodiment includes a milling step of milling raw talc with a steam jet mill. As mentioned above, the pulverization process using a steam jet mill uses superheated steam as the fluid energy for pulverization, so that high shear force can be applied instantaneously. Therefore, compared to a jet mill under general conditions using compressed air as the fluid energy, a shear force that is instantaneously larger than that of the raw talc powder acts on the raw talc powder, and the moisture on the surface is efficiently removed, resulting in good hydrophobicity. Therefore, when mixed with a resin to form a resin composition, it is considered that the inherent property improvement effect of the talc powder is easily expressed at a high level.
[0024] In the pulverization process using a steam jet mill, for example, the temperature of the superheated steam for steam jet mill pulverization (the temperature before entering the pulverization area) is preferably 300 to 500°C, and the pressure of the superheated steam (pulverization pressure) is preferably 3.5 to 15.0 MPa in terms of gauge pressure. By appropriately adjusting within the above ranges, the weight loss rate, bulk density, specific surface area, average particle size (D50), etc. can be set within the desired ranges. The superheated steam can be generated at a desired temperature using a commercially available boiler or superheater (steam superheater), etc.
[0025] The median diameter D0 of the raw material talc is preferably 11 to 20 μm, and the bulk density (solid) is preferably 0.3 to 1.5 g / cm 3 When the content is within these ranges, good grinding efficiency can be obtained, and the talc powder according to the present embodiment can be easily obtained.
[0026] The talc powder (pulverized talc powder) obtained as described above can be classified as necessary and used in various applications, particularly as a filler for addition to resins.
[0027] [Resin property improver] The resin property improver according to the present embodiment includes the talc powder according to the present embodiment. By mixing the resin property improver with a resin (for example, a thermoplastic resin described later), the resin property (particularly the elastic modulus) can be improved. That is, it is suitable as a resin property improver for addition to a resin (including a resin composition).
[0028] In order to fully exert its effects, the content of the talc powder according to this embodiment in the resin property improver is preferably 90% by mass or more, more preferably 95% by mass or more, and more preferably 100% by mass.
[0029] The resin property improver may contain, for example, a surface treatment agent such as a silane coupling agent or an acid-modified polymer (eg, maleic acid-modified PP).
[0030] [Resin composition] The resin composition according to this embodiment contains the talc powder according to this embodiment (or the resin property improver according to this embodiment) and a resin. Examples of the resin include thermoplastic resins (including thermoplastic elastomers for convenience), thermosetting resins, rubber, and cellulose-based resins.
[0031] Examples of the thermoplastic resin include olefin-based resins such as polypropylene, polyethylene, 4-methylpentene-1 resin, polybutene-1 resin, ethylene-propylene random copolymer, ethylene-propylene block copolymer, propylene-1-butene copolymer, propylene-ethylene-butene-1 copolymer, propylene-4-methylpentene copolymer, ethylene-butene-1 copolymer, ethylene-hexene copolymer, ethylene-heptene copolymer, ethylene-octene copolymer, ethylene-4-methylpentene copolymer, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, ethylene-methacrylic acid copolymer, and ethylene-methacrylic acid ester copolymer; styrene-based resins such as styrene homopolymer, acrylonitrile-styrene copolymer (AS resin), and acrylonitrile-butadiene-styrene copolymer (ABS resin); polyvinyl chloride, polyvinylidene chloride; polytetrafluoroethylene, ... Examples of the fluororesins include fluoroethylene-perfluoroalkyl vinyl ether copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene-tetrafluoroethylene copolymers, polychlorotrifluoroethylene resins, and polyvinylidene fluoride; polyvinyl alcohol; polyamide-based resins such as nylon 6, nylon 6,6, nylon 6,10, nylon 11, nylon 12, nylon 6,12, polyhexamethylenediamine terephthalamide, polyhexamethylenediamine isophthalamide, and xylene group-containing polyamides; polyester-based resins such as polyethylene terephthalate and polybutylene terephthalate; acrylic-based resins such as polymethyl acrylate and polymethyl methacrylate; polyoxymethylene-based resins such as polyoxymethylene homopolymers and polyoxymethylene copolymers; polycarbonate; polyacetal; polyphenylene ether; polyethersulfone; polyether ketone; and liquid polyester.
[0032] Examples of the thermoplastic elastomer include polyolefin-based thermoplastic elastomers, polystyrene-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, low-crystalline 1,2-polybutadiene-based thermoplastic elastomers, fluorine-based thermoplastic elastomers, chlorinated polymer-based thermoplastic elastomers, and ionically crosslinked thermoplastic elastomers.
[0033] Examples of the thermosetting resin include phenol resins, urea resins, melamine resins, alkyd resins, thermosetting acrylic resins, unsaturated polyester resins, diallyl phthalate resins, epoxy resins, thermosetting silicone resins, thermosetting polyimides, thermosetting resins derived from cyclopentadiene, thermosetting resins derived from aromatic nitriles; furan resins, ketone resins, xylene resins, and thermosetting resins containing condensed polycyclic aromatics.
[0034] Examples of the rubber include natural rubber, styrene butadiene rubber, butadiene rubber, chloroprene rubber, isoprene rubber, isobutylene-isoprene rubber, butyl rubber, ethylene propylene rubber, acrylonitrile butadiene rubber, nitrile rubber, silicone rubber, fluororubber, acrylic rubber, and epichlorohydrin rubber.
[0035] Examples of the cellulose-based resin include acetyl cellulose, acetyl propionyl cellulose, acetyl butyl cellulose, ethyl cellulose, and nitrocellulose.
[0036] The content of the talc powder according to one embodiment of the present invention is preferably 0.5 to 60 parts by mass, and more preferably 1 to 35 parts by mass, per 100 parts by mass of the resin in the resin composition.
[0037] The resin composition according to one embodiment of the present invention may contain one or more of antioxidants, heat stabilizers, weather resistance improvers, release agents, lubricants, pigments, dyes, plasticizers, antistatic agents, flame retardants, etc., as necessary. In addition, fillers other than the talc powder according to one embodiment of the present invention may be contained as necessary. Examples of such fillers include calcium carbonate, clay, synthetic silicon, titanium oxide, carbon black, barium sulfate, mica, glass fiber, whiskers, carbon fiber, magnesium carbonate, kaolin, graphite, molybdenum disulfide, zinc oxide, etc. Depending on the application, the resin composition may be made liquid by adding a solvent or a dispersion medium.
[0038] The talc powder can be blended and kneaded into the resin by a known method. For example, the talc powder can be blended and kneaded into the polypropylene by a commonly used single screw kneading extruder or twin screw kneading extruder. Furthermore, the resin composition according to this embodiment can be used for various applications such as automobile interior and exterior parts, home appliance parts, and office equipment parts. EXAMPLES
[0039] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these.
[0040] <Example 1, Comparative Example 1> [Talc powder] Median diameter (D50) is 13 μm, bulk density is 0.72 g / cm 3 The raw material talc 1 (talc produced in Pakistan was coarsely pulverized using a roller mill to give the above-mentioned D50) was pulverized to a median diameter of 5 μm using a steam jet mill (hereinafter sometimes referred to as "s-JET") and a jet mill, which will be described later. Example 1 is a talc powder obtained by s-JET, and Comparative Example 1 is a talc powder obtained by a jet mill.
[0041] <Example 2, Comparative Example 2> [Talc powder] Median diameter (D50) is 12 μm, bulk density is 0.67 g / cm 3 The raw material talc 2 (talc produced in China was roughly pulverized by a roller mill to the above-mentioned D50) was pulverized to a median diameter of 5 μm by each of a steam jet mill and a jet mill described later. Example 2 is a talc powder obtained by s-JET, and Comparative Example 2 is a talc powder obtained by a jet mill.
[0042] <Example 3, Comparative Example 3> [Talc powder] Median diameter (D50) is 13 μm, bulk density is 0.84 g / cm 3 The raw material talc 3 (talc produced in China was roughly pulverized by a roller mill to the above-mentioned D50) was pulverized to a median diameter of 5 μm by each of a steam jet mill and a jet mill described later. Example 3 is a talc powder obtained by s-JET, and Comparative Example 3 is a talc powder obtained by a jet mill.
[0043] <Example 4> [Talc powder] Median diameter (D50) is 17 μm, bulk density is 0.84 g / cm 3 The raw material talc 4 (talc produced in India was coarsely pulverized using a roller mill to give the above-mentioned D50) was pulverized using a steam jet mill described below to a median diameter of 5 μm to produce talc powder.
[0044] <Reference examples 1~3> The talc powders used in the resin compositions were commercially available products manufactured using jet mills from three different companies and were designated as talc powders in Reference Examples 1 to 3, respectively.
[0045] (1) Steam jet mill grinding conditions The equipment used was a Netzsch Trockenmahltechnik steam jet mill s-JET150. -Temperature of superheated steam (before entering the grinding area): 360℃ Grinding pressure (gauge pressure): 3.8MPa The particle size was adjusted by adjusting the rotation speed of a classifier attached to the steam jet mill.
[0046] (2) Jet mill grinding conditions The equipment used was a counter jet mill AFG710 / 4 manufactured by Hosokawa Micron Corp. Particle size adjustment was performed by adjusting the rotation speed of the classifier attached to the jet mill.
[0047] As shown in Table 1, s-JET produced bulky pulverized talc powder. On the other hand, the jet mill produced low-bulk pulverized talc powder when viewed at the same D50 as s-JET. This is thought to be because, with a jet mill under normal conditions, the pulverized powder has a long residence time, so that not only shear forces but also isotropic forces act on the talc, causing further pulverization rather than just surface peeling.
[0048] [Resin composition] The resin compositions prepared using the talc powders of the above examples were evaluated as follows.
[0049] Rating: Flexural modulus The flexural modulus was measured according to JIS K7171, and the results are shown in Table 2. The resin composition was injection molded using an injection mold (JIS K7171 Type B1), and the flexural modulus of the resulting molded product (10 mm (width) × 4 mm (thickness) × 80 mm (length)) was evaluated using an autograph AG-Xplus made by Shimadzu Corporation in accordance with JIS K7171 (temperature: 23°C, bending speed: 2 mm / min). The resin of the resin composition constituting the molded product was polypropylene resin (PX-600N from Sunallomer Co., Ltd.), and the amount of talc powder was 20 parts by mass per 100 parts by mass of polypropylene resin. The amount of stabilizer (Irganox B-225 from BASF Co., Ltd.) was 0.13 parts by mass per 100 parts by mass of polypropylene resin, and the amount of dispersant (calcium stearate from Tokyo Chemical Industry Co., Ltd.) was 0.13 parts by mass per 100 parts by mass of polypropylene resin.
[0050] Rating: Impact strength Based on JIS K7111-1, the Charpy impact strength (kJ / m) of the test piece (molded product prepared for measuring the flexural modulus) was measured at 23°C. 2 ) was measured.
[0051] [Table 1]
[0052] From Table 1, Examples 1 to 3, in which the weight loss rate was 0.180% by mass or less, were able to improve the resin properties more than the corresponding Comparative Examples 1 to 3. In other words, it can be said that they are suitable as a resin property improver for addition to a resin or a resin composition.
Claims
1. A talc powder having a weight loss rate of 0.180 mass% or less as measured by thermogravimetric differential thermal analysis at 100 to 450°C and a median diameter (D50) of 1 to 10 μm.
2. BET specific surface area: 3 to 20 m 2 2. The talc powder according to claim 1, wherein the molecular weight of the talc powder is 1 / g.
3. Bulk density: 0.10 to 0.35 g / cm 3 2. The talc powder according to claim 1,
4. A resin property improver comprising the talc powder according to any one of claims 1 to 3.
5. A resin composition comprising the talc powder according to any one of claims 1 to 3 and a resin.
Citation Information
Patent Citations
talc
JP2005104794A